1986
DOI: 10.1007/bf02553291
|View full text |Cite
|
Sign up to set email alerts
|

The changes in quality of mandibular bone mineral in otherwise totally immobilized Rhesus monkeys

Abstract: The status of bone mineral and osteocalcin in the young adult Rhesus monkey mandible was assessed following a 14-day period of postcranial immobilization, and after 7- and 28-day recovery periods. Specimens of cortical bone taken from the compact bone at the inferior border of the jaws were ground in liquid nitrogen and sieved to a particular size below 20 micron. The bone powder was then fractionated in a bromoform-toluene density gradient to determine its mineralization profile (Ca, P, CO3, and osteocalcin),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…X-ray diffraction has produced results for crystal length from 1 Dnm to 36nm (Myers and Engstrb'm, 1 965;Jackson et al, 1978;Engstrbm, 1972;Bonar et al, 1983;Boskey et al, 1985;Grynpas et al, 1986;Arsenault and Grynpas, 1988).…”
Section: Biological Apatitementioning
confidence: 99%
“…X-ray diffraction has produced results for crystal length from 1 Dnm to 36nm (Myers and Engstrb'm, 1 965;Jackson et al, 1978;Engstrbm, 1972;Bonar et al, 1983;Boskey et al, 1985;Grynpas et al, 1986;Arsenault and Grynpas, 1988).…”
Section: Biological Apatitementioning
confidence: 99%
“…However, several studies have suggested that a large component of the bone loss associated with disuse induced by HS is related to decreased bone formation, inhibition of mineralization, and delay in bone maturation (5,13,25,39,43,64,67). These changes in bone formation and maturation appear to be due, in part, to decreased proliferation and differentiation of osteoblast progenitors (26,33,56,57,71).…”
mentioning
confidence: 99%
“…By x-ray diffraction, crystal size has been found to range in its long dimension (c-axis) from 10-25 nm (Boskey et al, 1985;Grynpas et al, 1986). By electron microscopy, bone crystal length has been found to vary from 30-70 nm (Landis et al, 1978).…”
Section: Bone Mineralsmentioning
confidence: 98%